Monitoring the insertion of Pt into Cu2−xSe nanocrystals: a combined structural and chemical approach for the analysis of new ternary phases. Issue 31 (5th August 2020) - Casu, Alberto; Dalmases, Mariona; Lin, Mengxi; Wang, Yan; Homs, Narcís; Ramírez de la Piscina, Pilar; Llorca, Jordi; Figuerola, Albert; Falqui, Andrea
Abstract : The work explores the reactions between Cu2− x Se premade nanoparticles and a Pt(ii ) precursor, and confirms the formation of ternary CuPtSe phases with flexible stoichiometry and photocatalytic activity towards the hydrogen evolution reaction. Abstract : The tuning of the chemical composition in nanostructures is a key aspect to control for the preparation of new multifunctional and highly performing materials. The modification of Cu2− x Se nanocrystals with Pt could provide a good way to tune both optical and catalytic properties of the structure. Although the heterogeneous nucleation of metallic Pt domains on semiconductor chalcogenides has been frequently reported, the insertion of Pt into chalcogenide materials has not been conceived so far. In this work we have explored the experimental conditions to facilitate and enhance the insertion of Pt into the Cu2− x Se nanocrystalline lattice, forming novel ternary phases that show a high degree of miscibility and compositional variability. Our results show that Pt is mainly found as a pure metal or a CuPt alloy at high Pt loads (Pt : Cu atomic ratio in reaction medium >1). However, two main ternary CuPtSe phases with cubic and monoclinic symmetry can be identified when working at lower Pt : Cu atomic ratios. Their structure and chemical composition have been studied by local STEM-EDS and HRTEM analyses. The samples containing ternary domains have been loaded on graphite-like C3 N4 (g-C3 N4 ) semiconductor layers, and the resulting nanocomposite materials have been tested as promising photocatalysts for the production of H2 from aqueous ethanolic solutions.